ABO blood group and link to COVID-19: A comprehensive review of the reported associations and their possible underlying mechanisms. (August 2022) - Pereira, Eric; Felipe, Stela; de Freitas, Raquel; Araújo, Valdevane; Soares, Paula; Ribeiro, Jannison; Henrique dos Santos, Luiz; Alves, Juliana Osório; Canabrava, Natália; van Tilburg, Mauricio; Guedes, Maria Izabel; Ceccatto, Vânia
Abstract: ABO blood group is long known to be an influencing factor for the susceptibility to infectious diseases, and many studies have been describing associations between ABO blood types and COVID-19 infection and severity, with conflicting findings. This narrative review aims to summarize the literature regarding associations between the ABO blood group and COVID-19. Blood type O is mostly associated with lower rates of SARS-CoV-2 infection, while blood type A is frequently described as a risk factor. Although results regarding the risk of severe outcomes are more variable, blood type A is the most associated with COVID-19 severity and mortality, while many studies describe O blood type as a protective factor for the disease progression. Furthermore, genetic associations with both the risk of infection and disease severity have been reported for the ABO locus . Some underlying mechanisms have been hypothesized to explain the reported associations, with incipient experimental data. Three major hypotheses emerge: SARS-CoV-2 could carry ABO(H)-like structures in its envelope glycoproteins and would be asymmetrically transmitted due to a protective effect of the ABO antibodies, ABH antigens could facilitate SARS-CoV-2 interaction with the host' cells, and the association of non-O blood types with higher risks of thromboembolic events could confer COVID-19 patients with blood type O a lower risk of severe outcomes. The hypothesized mechanisms would affect distinct aspects of the COVID-19 natural history, with distinct potential implications to the disease transmission and its management. Highlights: The ABO blood group comprises carbohydrate antigens and their related antibodies. ABO blood types are known to influence the susceptibility to infectious diseases. The ABO blood group has been associated with SARS-CoV-2 infection and its severity. Some underlying mechanisms are potentially involved, with distinct implications.